Phosphorofluoridic Acid as an Efficient Catalyst for One Pot Synthesis of Dihydropyrimidinones under Solvent Free and Ambient Condition. (2019) - Mathapati, Sushil R.; Prasad, Divya; Atar, Amol B.; Mallanna Nagaraja, Bhari; Dawle, Jairaj k.; Jadhav, Arvind H.
Abstract: An efficient and simple protocol has been developed for the synthesis of 3, 4-dihydropyrimidin-2-ones (DHPMs) from aldehydes, ethyl acetoacetate and urea using phosphorofluridic acid as the catalyst under solvent free conditions. In comparison with the classical Biginelli reaction, with the given conditions and catalysts, 10 mol% of phosphorofluroridic acid showed excellent catalytic activity. This method has the advantage of being eco-friendly, has an easy work up process and produces high yields in short reaction time.